KUALITAS LAGU TERJEMAHAN “NE PARLONS PAS DE BRUNO” PADA FILM ANIMASI “ENCANTO” - Mardalena, Ismirani; Antsar Nys, Muhammad Albany (Jurnal Penerjemahan, 2025)
Translating songs presents a unique challenge for translators because, in addition to preserving the meaning, they must ensure the text is singable. This is especially crucial for animated film soundtracks and musicals, where songs not only set the tone but also advance the plot (Ahmed, 2022). This study aims to identify the translation strategies applied to the soundtrack titled “Ne Parlons Pas de Bruno”” in the movie “Encanto”, using André Lefevere’s (1975) theory of poetry translation. After identifying the strategies used, this study applies the Pentathlon Principle proposed by Peter Low (2005) to assess the translation. The analysis reveals that the translated song “Ne Parlons Pas de Bruno” achieves a balanced score according to Low’s (2005) framework, with the metrical and interpretation strategies being the most frequently used strategies. These findings suggest that the most appropriate strategies for translating movie soundtracks are metrical and interpretation strategies.